Evolving Food Safety Pressures in California's Central Coast Region - Olimpi, Elissa M.; Baur, Patrick; Echeverri, Alejandra; Gonthier, David; Karp, Daniel S.; Kremen, Claire; Sciligo, Amber; De Master, Kathryn T. (Frontiers in Sustainable Food Systems, 2019)
California’s Central Coast rose to national food safety prominence following a deadly 2006 outbreak of Escherichia coli O157:H7 that was traced to spinach grown in this intensive agricultural region. Since then, private food safety protocols and subsequent public regulations targeting farm-level practices have developed extensively, aiming to avert future foodborne illness crises. However, amidst sweeping reforms in prescribed best practices for food safety, growers were pressured to take precautionary approaches to control pathogenic contamination—suppressing wildlife near fields, removing habitat, restricting biological soil amendments (e.g., compost, manure), and most recently, chemically treating irrigation water—that may generate negative unintended consequences for environmental and social sustainability. We synthesize socio-ecological data from three qualitative, interview-based studies to examine grower perceptions and experiences of food safety reforms in California’s Central Coast region and explore the effects of food safety regulations on environmental and socio-economic sustainability. We identify three disjunctures between food safety requirements and farming realities in practice: 1) Growers perceive that some food safety practices legitimately mitigate risk, while others fail to reduce or even accentuate risk; 2) Food safety requirements can create contradictions in the co-management of food safety and environmental sustainability; and 3) Food safety requirements may foster impediments to regional food systems socioeconomic sustainability. We argue that these disjunctures warrant changes in food safety policy, implementation, and/or food safety education. We provide concrete suggestions for shifting the focus of food safety reform away from the narrow surveillance of individual grower compliance and toward an integrated perspective on regional risk, vulnerability, and resilience.